Büyüyen Korku: Mobil Telefon Yoksunluğu Korkusu (Nomofobi) Üzerine Bir Çalışma. - YOLCU, Pelin; ÇİFTÇİ, Hasan (Itobiad: Journal of the Human & Social Science Researches / İnsan ve Toplum Bilimleri Araştırmaları Dergisi, 2023)
[With the rapid development of technology in the age of technology, people's lifestyles have also changed. It has become possible for people to meet all their needs through technology. Today, developing technology has introduced some addictions into our lives. Akıllı telefon bağımlılığı, akıllı telefonların hayatımıza girmesiyle birlikte görülen bu durum günlük hayatta dikkat çekici bir hal almıştır. In the digital age we live in, almost every transaction is carried out via smartphones. For this reason, mobile phones have become an indispensable part of today. The main purpose of this research is to determine the nomophobia levels of Vocational School students. Another aim of the study is to compare the nomophobia levels of students according to different variables. The survey technique, one of the quantitative data collection techniques, was used in the study. The study group of the research consists of 353 students studying at Harran University Birecik Vocational School Computer Technologies Department Computer Programming in the 2022-2023 academic year. In this context, in the study, a survey was applied to 353 students using the NMP-Q scale, which was adapted into Turkish by Yıldırım et al. (2016). The obtained data were analyzed from Independent Sample T Test and One Way Anova (analysis of variance) using SPSS 22.0 Statistical Analysis Program. The dimension that the participants perceived at the highest level is the dimension of losing communication (Mean= 3.26). Therefore, it can be said that vocational school students have a fear of losing communication. As a result of the research, a statistically significant difference was found in the nomophobia levels of the students in terms of gender. In this context, it was determined that the averages of women were higher than men in all dimensions. When the nomophobia levels are examined according to the class variable; A statistically significant difference was found in the dimensions of not being able to access information and not being online. When the nomophobia levels are examined in terms of the age variable; It has been determined that there is a statistically significant difference in the dimensions of not being able to access information and deprivation of a device, and when it is examined according to the income variable, only in the dimension of not being able to go online.and pasted here.